p53 status modifies cytotoxic activity of lactoferrin under hypoxic conditions - Kosim, Maryami Yuliana; Fukazawa, Takahiro; Miyauchi, Mutsumi; Hirohashi, Nobuyuki; Tanimoto, Keiji (Frontiers in Pharmacology, 2022)
Lactoferrin (LF) is an iron binding glycoprotein of the transferrin family with a wide spectrum of biological effects, including anti-cancer activity. However, the detailed molecular mechanisms of anti-cancer activity of LF have not been fully determined. In this study, we tried to clarify cytotoxic functions of LF on various cell lines under hypoxic conditions and elucidate those molecular mechanisms. MTT assays demonstrated cytotoxic activity of LF on cell lines with a range of sensitivities to LF. Hypoxia decreased sensitivity to LF in KD but increased that in HSC2. Expression analyses further revealed that LF treatments enhanced hypoxic HIF-1α protein stabilization in KD but attenuated that in HSC2 cells and decreased HIF-1 target gene, DEC2, in KD but increased that in HSC2, suggesting a possible relationship between LF-modified DEC2 expression and HIF-1α protein. A further MTT assay strikingly demonstrated that cells expressing mutant type p53 (MT5) were more sensitive to LF than control HepG2 (C4), suggesting an important role of the p53 signal. Knock down of TP53 interestingly reduced sensitivity to LF in HepG2, suggesting that p53 signal may be a target of LF cytotoxic activity. Further analyses with a ferroptosis promoter or inhibitor demonstrated that LF treatments increased ACSL4 in hypoxic MT5, suggesting LF-induced ferroptosis in cells expressing mutant type p53. In conclusion, hypoxia was found to regulate cytotoxic activities of LF differently among various cell lines, possibly through the p53 signaling pathway. LF further appeared to regulate ferroptosis through a modification of ACSL4 expression downstream of p53.